2021
DOI: 10.1021/acs.analchem.1c03431
|View full text |Cite
|
Sign up to set email alerts
|

Exponential Increase in an Ionic Signal: A Dominant Role of the Space Charge Effect on the Outer Surface of Nanochannels

Abstract: Nanochannels have advantage in sensitive analyses due to the confinement effects on ionic signal in nano-or subnanometric confines but could realize further gains by optimizing signal mechanism. Making target recognitions on the outer surface of nanochannels has been verified to improve target recognitions and signal conversions by maximizing surfaces accessible to targets and ions, but until recently, the signal mechanism has been still unclear. Using electroneutral peptide nucleic acid (PNA) and negative-cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 61 publications
(97 reference statements)
0
12
0
Order By: Relevance
“…Furthermore, the experimental results showed that the ICR ratio decreased with the pore size of the PET nanochannels (Figure S12), which stem from the space compression of the ion-enrichment/depletion region and the corresponding enhancement of the double-layer interaction. 73,74 Both the experimental and theoretical results demonstrated that the change in surface charge by modified PDA in the ion-depletion region leads to the fundamental change in the ICR effect.…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…Furthermore, the experimental results showed that the ICR ratio decreased with the pore size of the PET nanochannels (Figure S12), which stem from the space compression of the ion-enrichment/depletion region and the corresponding enhancement of the double-layer interaction. 73,74 Both the experimental and theoretical results demonstrated that the change in surface charge by modified PDA in the ion-depletion region leads to the fundamental change in the ICR effect.…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…For a long time, people ignored FE OS , so that its functions were not clear. We carried out research on the precise functional zoning of solid-state nanopores and focused on the role of FE OS in ion gating (Figure c). By controllably depositing metal layers using an electron-beam evaporation technique, only the one outer surface of the nanopores was modified (Figure a). For example, a thick gold layer was sputtered onto one side of the anodic aluminum oxide nanopore membrane, and the capture probe was immobilized to the outer surface through Au–S chemistry for regulating ion gating after the formation of a self-assembled DNA monolayer .…”
Section: Outer Surface Modified Nanoporesmentioning
confidence: 99%
“…FE OS such as negatively charged DNA causes an exponential increase in an ionic signal by the space charge effect. 16 DNA rolling circle amplification on the outer surface of nanopores achieves single-base mismatch detection of mRNA-21 with a sensitivity of 6 fM. 17 FE OS can effectively improve the ion selectivity and output power of nanopores without increasing the internal resistance.…”
Section: ■ Outer Surface Modified Nanoporesmentioning
confidence: 99%
See 1 more Smart Citation
“…Specific recognition moiety-functionalized solid-state nanofluidic channels have been shown to be selective and sensitive sensors for various analytes. Steady-state current change with chemical composition, surface charge, wettability, and the diameter of the nanofluidic channel caused by even a single molecule can be efficaciously recorded, endowing nanofluidic sensors with sensitivity down to aM levels. , The introduction of various specific recognition moieties including aptamer, phenylboronic acid, antibodies, and functional metal–organic frameworks brings the nanofluidic channel target-specific selectivity. , However, the time-consuming interaction of the recognition moieties and the targets is a great limitation for the application of nanofluidic channel-based sensors in rapid detection. , Thus, promoting the kinetics for the interaction between the analyte and the recognition moiety on the nanofluidic channels is the key to overcome the limitation.…”
Section: Introductionmentioning
confidence: 99%